Bless me, Ultima - Anaya, Rudolfo A. (Warner Books, 1999)
Six-year-old Antonio embarks upon a spiritual journey under the watchful guidance of Ultima, a healing woman, that leads him to question his faith and beliefs in family, religion, and other aspects of his Chicano culture.